The Influence of Nurse Behavior on the Completeness of Nursing Care Filling - Sari, Maya Kartika (Newinera Publisher, 2024)
Completeness of nursing care is a professional need that needs to be taken into consideration from both an ethical and legal standpoint. This study aimed to analyze the influence of knowledge, attitudes, actions, motivation, workload and the most influential factor on the completeness of nursing care completion at Sufina Aziz Hospital Medan. This is quantitative research using cross-sectional design. The study population was all executive nurses and the sample used 55 executive nurses taken by using total sampling technique. The result of univariate test of good knowledge was 43 people (78.2%), positive attitude was 42 people (76.4%), good action was 7 people (12.7%), strong motivation was 45 people (81.8%), heavy workload was 16 people (29.1%), completeness of nursing care completion with good category was 36 people (65.5%). Chi Square test Sig value with knowledge variable was 0.050 and the attitude value was 0.003 because the p value <0.05, it could be concluded that there was a relationship while the logistic regression test the variable that had the most influence on the completeness of nursing care completion was the attitude variable with a Sig. value of 0.005 (p <0.05).The conclusion shows that the attitude of executive nurses is 22 times at risk of the completeness of nursing care completion at Sufina Aziz Hospital Medan. To ensure that nursing care is provided in line with nursing care standards, it is advised that the executive nurse receive regular monitoring and evaluation for completing nursing care forms completely, properly, and on time.